Activation of ferritinophagy is required for the RNA-binding protein ELAVL1/HuR to regulate ferroptosis in hepatic stellate cells. Issue 12 (2nd December 2018) - Zhang, Zili; Yao, Zhen; Wang, Ling; Ding, Hai; Shao, Jiangjuan; Chen, Anping; Zhang, Feng; Zheng, Shizhong
ABSTRACT: Ferroptosis is a recently recognized form of regulated cell death that is characterized by lipid peroxidation. However, the molecular mechanisms regulating ferroptosis are largely unknown. In this study, we report that the RNA-binding protein ELAVL1/HuR plays a crucial role in regulating ferroptosis in liver fibrosis. Upon exposure to ferroptosis-inducing compounds, ELAVL1 protein expression was remarkably increased through the inhibition of the ubiquitin-proteasome pathway. ELAVL1 siRNA led to ferroptosis resistance, whereas ELAVL1 plasmid contributed to classical ferroptotic events. Interestingly, upregulated ELAVL1 expression also appeared to increase autophagosome generation and macroautophagic/autophagic flux, which was the underlying mechanism for ELAVL1-enhanced ferroptosis. Autophagy depletion completely impaired ELAVL1-mediated ferroptotic events, whereas autophagy induction showed a synergistic effect with ELAVL1. Importantly, ELAVL1 promoted autophagy activation via binding to the AU-rich elements within the F3 of the 3ʹ-untranslated region of BECN1/Beclin1 mRNA. The internal deletion of the F3 region abrogated the ELAVL1-mediated BECN1 mRNA stability, and, in turn, prevented ELAVL1-enhanced ferroptosis. In mice, treatment with sorafenib alleviated murine liver fibrosis by inducing hepatic stellate cell (HSC) ferroptosis. HSC-specific knockdown of ELAVL1 impaired sorafenib-induced HSC ferroptosis in murine liver fibrosis. Noteworthy, we retrospectively analyzed the effect of sorafenib on HSC ferroptosis in advanced fibrotic patients with hepatocellular carcinoma receiving sorafenib monotherapy. Attractively, ELAVL1 upregulation, ferritinophagy activation, and ferroptosis induction occurred in primary human HSCs from the collected human liver tissue. Overall, these results reveal novel molecular mechanisms and signaling pathways of ferroptosis, and also identify ELAVL1-autophagy-dependent ferroptosis as a potential target for the treatment of liver fibrosis. Abbreviations: ACTA2/alpha-SMA: actin, alpha 2, smooth muscle, aorta; ACTB/beta-actin: actin beta; ARE: AU-rich element; ATG: autophagy related; BDL: bile duct ligation; BECN1: beclin 1; BSO: buthionine sulfoximine; COL1A1: collagen type I alpha 1 chain; ELAVL1/HuR: ELAV like RNA binding protein 1; FDA: fluorescein diacetate; FTH1: ferritin heavy chain 1; GOT1/AST: glutamic-oxaloacetic transaminase 1; GPT/ALT: glutamic–pyruvic transaminase; GPX4: glutathione peroxidase 4; GSH: glutathione; HCC: hepatocellular carcinoma; HSC: hepatic stellate cell; LCM: laser capture microdissection; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MDA: malondialdehydep; NCOA4: nuclear receptor coactivator 4; PTGS2: prostaglandin-endoperoxide synthase 2; ROS: reactive oxygen species; SQSTM1/p62: sequestosome 1; TBIL: total bilirubin; TEM: transmission electron microscopy; TGFB1: trasforming growth factor beta 1; UTR: untranslated region; VA-Lip- ELAVL1 -siRNA: vitamin A-coupled liposomes carrying ELAVL1 -siRNA.